2020
DOI: 10.3390/su12041577
|View full text |Cite
|
Sign up to set email alerts
|

Greening Vienna. The Multi-Level Interplay of Urban Environmental Policy–Making

Abstract: Vienna is widely recognised as an example of urban sustainability, crowned as one of the most liveable cities worldwide by several quality of life rankings. Despite being highly committed to incorporating the ecological and social dimension into its urban development strategy, Vienna is undergoing a deep transition, orienting its urban policy more closely toward economic criteria and techno-managerial solutions to climate change. While European capitals have been extensively studied, research on Vienna's envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In the last decade, this trend is being reinforced since Vienna started to experience steep population growth. Indeed, a combination of massive in-migration and economic growth policies led the local authority to turn again towards urban expansion (Mocca, Friesenecker, and Kazepov 2020). Not to mention the fact that urban expansion stands in opposition to degrowth narratives, as explored by Exner (2018) already, but Vienna aims to transform brownfield sites rather than use greenfield sites for urban expansion.…”
Section: Recent Trends In Viennese Housing Policy: Differentiated Forms Of Collaborative Housingmentioning
confidence: 99%
“…In the last decade, this trend is being reinforced since Vienna started to experience steep population growth. Indeed, a combination of massive in-migration and economic growth policies led the local authority to turn again towards urban expansion (Mocca, Friesenecker, and Kazepov 2020). Not to mention the fact that urban expansion stands in opposition to degrowth narratives, as explored by Exner (2018) already, but Vienna aims to transform brownfield sites rather than use greenfield sites for urban expansion.…”
Section: Recent Trends In Viennese Housing Policy: Differentiated Forms Of Collaborative Housingmentioning
confidence: 99%
“…Looking back at the three analyzed cities, we have observed that a holistic approach to both Smart City strategies and adaptation to climate change is of vital importance, as integrated urban systems will make the governance of traditionally separate but interdependent urban services less complex and more efficient [30]. In the case of Vienna, we have found that adaptive cities can also benefit from the Smart City approach, as the Smart City Wien Framework has unified various separate initiatives under the Smart City umbrella [58], leading to a surge in funded Smart Environment projects [51,56]. Rotterdam is becoming more adaptive to climate hazards due to new technologies, which contribute to faster and more accurate decision-making in the struggle against sea-level rise [47].…”
Section: Discussionmentioning
confidence: 96%
“…In 2017, however, the initiative Adapting to Climate Change in Vienna [49] was launched under Vienna's broader Climate Protection Programme, KLiP Wien, which has already been active for over two decades (although with more focus on the reduction of CO2). Still, there is a lack of research in urban studies that concern Vienna's adaptation strategies [58]. Even so, the Adapting to Climate Change in Vienna initiative points out that more attention will be paid to the extension of green spaces and the creation of more shade spots in order to better address Vienna's vulnerability to extreme heat [49].…”
Section: Adaptation On the City Levelmentioning
confidence: 99%
See 2 more Smart Citations